Enforcement Of Criminal Acts Of Violence Threats On Social Media Based On Article 29 Paragraph (1) Of The Information And Electronic Transactions Law - Yurike Revina Maharani; Yudi Fahrian; Suryani Yusi (Jurnal Multidisiplin Dehasen (MUDE), 2026)
This study discusses the law enforcement of criminal acts of threats of violence on social media based on Article 29 Paragraph (1) of Law Number 1 of 2024 concerning Electronic Information and Transactions (ITE). The purpose of this research is to identify the legal implications of threats of violence through electronic media and the factors hindering law enforcement. The research method used is normative legal research with a statute approach and a conceptual approach. The results indicate that Article 29 Paragraph (1) of the ITE Law has expanded protection for victims by clarifying the phrase "directly to the victim," but the phrase "scares" remains open to multiple interpretations. Other obstacles are identified in the substance, structure, and culture of the law, particularly the low digital literacy of the public and the limitations of law enforcement officials in handling cybercrime. This research recommends revising legal norms to be more stringent, increasing the capacity of law enforcement officials, and strengthening digital literacy to prevent threats of violence in the digital space.